2010
DOI: 10.1002/jmv.21797
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of HIV‐1 non‐B subtype infections in Northwest Poland

Abstract: The number of non‐B subtype HIV‐1 infections in Europe has been increasing even though major regional differences have been observed. This trend was investigated in northwestern Poland using sequence and epidemiological data from a cohort of 102 HIV‐1‐infected patients from Szczecin, Poland. HIV‐1 subtypes were defined by phylogenetic analysis of viral reverse transcriptase‐ and protease‐partial coding regions, and results were compared with online subtyping by Standford and REGA tools. Subtype analysis using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Up until 1999, only B clade was detected in Polish HIV-1 infected individuals and mainly occurred in MSM (42%) and PWID (35%). Non-B clades (namely A1, C, D and F1) were introduced later and detected more frequently among heterosexuals and females (Parczewski et al, 2012;Parczewski et al, 2010;Parczewski et al, 2016). Similarly in the Czech Republic and Slovakia, non-B strains were found almost exclusively in heterosexuals (Chabadova et al, 2014;Linka et al, 2008;Reinis et al, 2001).…”
Section: Central Europementioning
confidence: 96%
“…Up until 1999, only B clade was detected in Polish HIV-1 infected individuals and mainly occurred in MSM (42%) and PWID (35%). Non-B clades (namely A1, C, D and F1) were introduced later and detected more frequently among heterosexuals and females (Parczewski et al, 2012;Parczewski et al, 2010;Parczewski et al, 2016). Similarly in the Czech Republic and Slovakia, non-B strains were found almost exclusively in heterosexuals (Chabadova et al, 2014;Linka et al, 2008;Reinis et al, 2001).…”
Section: Central Europementioning
confidence: 96%
“…This cluster of heterosexually acquired infections seemed independent from subtype B ones spreading among men who have sex with men (MSM),injection drug users (IDU) and heterosexual populations [27]. Dated phylogeny and phylogeographic analyses suggested that the tMRCA of the subtype D found in Poland is 1989.2 (95% HPD: 1994.46–1968.83) and is of Ugandan origin.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously identified higher prevalence of non-B subtypes, with a number of subtype D clades in the local population from Northwestern Poland (21%). These variants have been associated with more advanced HIV disease and more common heterosexual transmission route if compared to the subtype B [27].…”
Section: Introductionmentioning
confidence: 99%
“…Genotypic susceptibility scores (GSS) were calculated based on mutation scores obtained from this database with modifications described by Anderson et al [2008]. HIV-1 subtypes were characterized using the phylogenetic method using reference sequences from the HIV Sequence Compendium 2009 as described previously [Parczewski et al, 2010].…”
Section: Genotyping Procedures and Data Interpretationmentioning
confidence: 99%